Problematika Hukum Pagar Laut yang Berdampak pada Mata Pencaharian Nelayan di Tangerang, Banten - Amalia, Selma Dwi; Gulshan, Nadia; Ningrum, Chantika Gina; Izazqi, Radhitya (Forschungsforum Law Journal, 2025)
Abstract: Various legal, economic, social, and environmental issues have arisen due to the construction of a 30.16-kilometer-long sea barrier in the waters of Tangerang. The presence of this barrier prevents fishermen from accessing their fishing grounds, leading to a decline in fish catch, increased operational costs, and frequent vessel damage. Additionally, the sea barrier negatively impacts the marine ecosystem by disrupting water flow and accelerating sedimentation, which can harm marine habitats. From a legal perspective, the sea barrier violates several national laws and international law under UNCLOS. This study employs a normative juridical method with a statutory and case study approach. The findings indicate that the construction of the sea barrier benefits business interests more than the well-being of coastal communities, contradicting the principles of social justice and public interest. Therefore, the government must take firm legal action and implement policies that prioritize the interests of affected communities to mitigate the negative social and environmental impacts of the sea barrier. Keywords: Sea Barrier, Fishermen, Maritime Law, Social Justice, UNCLOS.